Improving Vocational Students' Outlining Skills Through Perplexity AI - Diah Amaliya Nuraini; Fahri Fahri (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Outlining is an important part of analytical exposition writing, which enables students to plan and organize their ideas. However, the students' arguments in vocational high schools are not organized well, and research on AI-assisted outlining has been limited in vocational secondary education. This study aimed to investigate the impact of the outlining instruction using Perplexity AI on students' outlining skills for analytical exposition texts. The quasi-experimental pre test – post test design involving 64 vocational high school students in grade 10 was used. Students’ outlining performance was assessed using an analytic outlining rubric. Improvements were found in both groups, with the experimental group significantly outperforming the control group. An independent-sample t-test found significant gain scores (p < .05), and effect size analysis showed a very large effect (Cohen’s d = 1.05). The results indicate that the use of Perplexity AI is an effective tool for outlining performance on EFL writing tasks.